2007
DOI: 10.1177/1523422306294492
|View full text |Cite
|
Sign up to set email alerts
|

A Strategic Perspective on Human Resource Development

Abstract: The problem and the solution. This article reviews the literature on strategic human resource development. It proposes a model of strategic Human Resource Development (HRD) which is multi-level and focuses on the interactions between context, HRD processes, stakeholder satisfaction, and characteristics of the HRD profession. The article discusses the implications of this model for both research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
263
0
22

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(290 citation statements)
references
References 40 publications
5
263
0
22
Order By: Relevance
“…For instance, Denis et al (2001) reported a see-saw theory of strategic change and managerial leadership implying the need to identify generative mechanisms or forces of coupling or alignment. This study deals with forces of alignment in terms of strategic HR practices that refer to different layers of strategic change as indicated by the distinction of resource flows associated with a changing of the HRD system architecture in either an administrative or strategic pattern (Garavan 2007;Ridder et al 2012a, b) and aligning HR (stock) development to capability reconfiguration (Clardy 2008;Kang et al 2007). One limitation is that this study is based on a specific setting representing German local government; additionally that data analysis focuses strategic HRD in a context of managing accounting change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Denis et al (2001) reported a see-saw theory of strategic change and managerial leadership implying the need to identify generative mechanisms or forces of coupling or alignment. This study deals with forces of alignment in terms of strategic HR practices that refer to different layers of strategic change as indicated by the distinction of resource flows associated with a changing of the HRD system architecture in either an administrative or strategic pattern (Garavan 2007;Ridder et al 2012a, b) and aligning HR (stock) development to capability reconfiguration (Clardy 2008;Kang et al 2007). One limitation is that this study is based on a specific setting representing German local government; additionally that data analysis focuses strategic HRD in a context of managing accounting change.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Luoma (2000) and others (Clardy 2008;Garavan 2007) differentiate the HRD plans and procedures to enhance an organization's HR stock, the HRD function among others in the organization, or the certain outcome state of HRD, that is increasing the applicability of employee skills and knowledge to organizational objectives. The resource-based view adds a somewhat different approach.…”
Section: Contextual Analysis: Archetypes Of Accounting Changementioning
confidence: 99%
“…It also seems unlikely that current qualifications will remain sufficient for administrative middle-managers. The lack of development goes against the rhetoric of lifelong learning and resource based strategy about investing in human resources (Garavan 2007). The lack of learning, development and mobility is of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the 'what' and 'why' questions can build understanding of the components of alignment that organizations recognize at the formulation, implementation and evaluation stages of the alignment process. While extant literature highlights the benefits of alignment generally, or in relation to functions such as human resources or IT (Garavan 2007), there is a lack of research on these issues for values-driven business. By revealing the areas in which there are overlaps or failure to leverage the work of values-driven business functions and organizations' views of the negative consequences or potential benefits of alignment, there is an opportunity for scholars to critically examine organizations' priorities and reasons to integrate values-driven business.…”
Section: A Model For Values-driven Business Alignment: Questions To Imentioning
confidence: 99%